Influences on Participation in Life After Spinal Cord Injury: Qualitative Inquiry Reveals Interaction of Context and Moderators - Amsters, Delena; Kendall, Melissa; Schuurs, Sarita; Kuipers, Pim (Frontiers in Rehabilitation Sciences, 2022)
Abstract Background Greater understanding of the influences on participation in life after spinal cord injury (SCI) can inform rehabilitation theory and practice. Careful qualitative inquiry can reveal subjective meanings associated with the relevant experiences, strategies, and perceptions of those with lived experience of SCI. A search of literature, followed by a thematic synthesis of qualitative studies, was undertaken to bring together these insights in a meaningful way. Methods The research question guiding the literature review and synthesis was, What do people with SCI perceive to be the influences on their participation in life? Three critical databases were searched for qualitative studies examining influences on participation in life after SCI. Peer-reviewed studies published after 2006, involving adults with SCI living in countries with advanced economies were included. Data were extracted from 24 articles and subjected to three-level thematic synthesis – the coding of primary data from the studies, the development of descriptive themes based on an organization of those codes, and the generation of analytical themes. Results The synthesis yielded five analytical themes, supported by 18 descriptive themes. The analytical themes were 1) external contextual influences, 2) personal physical context, 3) personal psychological context, 4) potential moderators of participation outcomes, and 5) temporal dimensions of participating in life after SCI. Interpretation These themes highlight the complex interactions that shape participation from the perspective of people with SCI. Closer examination of the potential moderators may provide insights into effective rehabilitation interventions. Conclusions Synthesis of qualitative inquiry provides valuable insights into the perceptions of influences on participation in life from the point of view of people with SCI. The findings of this synthesis are instructive for rehabilitation theory and practice. It can complement what we learn from using the ICF to understand participation.